Clinical profile and management outcomes of lacrimal drainage system malignancies. (4th July 2022) - Alam, Md. Shahid; Mukherjee, Bipasha; Krishnakumar, Subramanian
ABSTRACT: Purpose: To report the clinical profile and management outcomes of a series of cases of malignant tumors of the lacrimal drainage system (LDS). Materials and Methods: A retrospective analysis of all cases diagnosed with LDS malignancy over the past 24 years (1995–2019) was done. Patient characteristics, tumor types, management, and outcomes were analyzed. Results: A total of 14 patients were included. Thirteen cases were of primary malignancy, while one was a secondary lesion. The mean age was 42.5 years, with males and females being equally affected. A medial canthal mass was the most common (9, 64.2%) presentation. Six patients (42.8%) had undergone one or more dacryocystorhinostomy surgeries for nasolacrimal duct obstruction before presentation. Seven patients underwent wide local excision (50%) while 3 (21.4%) each underwent dacryocystectomy and exenteration. Adjuvant radiation was administered to 4 (28.5%) patients. Thirteen (92.8%) patients were diagnosed with epithelial malignancy while one (7.1%) was a case of small B cell lymphoma. Transitional cell carcinoma was the most common epithelial malignancy (4, 28.5%). Three (21.4%) patients had metastatic disease (2 lymph nodes and one angle of jaw). There was no mortality after a mean follow up of 40.7+_25.1 months (Median 26; Range 4–131). Conclusion: LDS malignancy is rare, with the epithelial variant being far more common than non-epithelial. Wide local excision with adjuvant radiotherapy is the preferred management. Long-term follow-up is essential to manage recurrences and to increase survival.